Love Enough! Dionne Brand and Rosi Braidotti’s Affective Transpositions - García Zarranz, Libe (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This article puts Dionne Brand’s novel, Love Enough (2014), in conversation with the vitalist philosophy of Rosi Braidotti, as illustrated in the study Transpositions: On Nomadic Ethics (2006). I look at how both poet and theorist insist on the centrality of affective relations in the transformation of subjectivity, political alliances, and ethical spaces under processes of uneven globalization, rampant neoliberalism, and feminist backlash. Dionne Brand’s cross-border material poetics proposes alternative figurations of the subject through exercises of creative repetition, zigzagging between temporal and spatial frameworks, signaling the constant transformation of material, political and social bodies. Brand’s transposable moves follow a similar pattern to Braidotti’s nomadic cartographies in that both resist a naïve return to sentimentality or nostalgic love to advocate instead a turn to sustainable affects and passions; a call for love as a mode of action that can reorient the system by embracing our potential as feminist subjects.